Implementasi Prinsip Fair Trade oleh The Body Shop sebagai Upaya Peningkatan Kesejahteraan Masyarakat Rwanda - Kathleen Mintarja; Priscilia Christian Kadim; Stella Claresta Alexander (Jurnal Sentris, 2019)
The second half of the twentieth century witnessed unprecedented growth in the number of international actors. There has been a dramatic increase in the number of non-state actors that, on many occasions, helped solve problems and improve lives. This makes the responsibility of people’s welfare no longer only held by the government. One of the most prominent examples is the role of Body Shop on improving the living standard of Rwandan. Twenty four years after the genocide that killed almost 800,000 people, the country of Rwanda is rebuilding with the support of international communities, including multinational corporations. The Body Shop’s Community Trade commitment has been a key part of bringing local producers into international supply chains and empowering them. Therefore, the research question in this paper is “How is the role of The Body Shop on implementing fair trade principles towards the Rwandan society?” To answer the research question, the authors use several theories and concepts; such as pluralism, multinational companies, and fair trade theory. In addition, the research method to be used by the authors is a qualitative study method. This research found that The Body Shop has launched a Moringa Community Trade program as an embodiment of efforts to improve the welfare of Rwandan people after the genocide occurred. This community trade initiative aims to be one small step forward to achieve financial stability for the people currently living and working in Rwanda.